Ultrasound-Guided Erector Spinae Plane Block versus Oblique Subcostal Transversus Abdominis Plane Block for Post-Operative Analgesia of Adult Patients Undergoing Laparoscopic Cholecystectomy - Ali, Muhammad; Bilal Yasin; Sidra Khan; Iftikhar Ali; Hassam Abdullah; Humayun Munir Tarar (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the relative effectiveness of Oblique subcostal transversus abdominis plane block with Erector spinae plane block in reliving post-operative pain in patients subjected to elective laparoscopic cholecystectomy.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Anaesthesiology, Combined Military Hospital, Rawalpindi Pakistan, from Nov 2020 to Apr 2021.Methodology: Sixty-eight patients were equally divided into two groups, ESP and OSTAP (34 each). ESP-Group received a bilateral erector spinae block, and OSTAP-Group received a bilateral oblique subcostal transversus abdominis block. Ultrasound guidance was used for block execution in both Groups. Bupivacaine 0.375% 20 ml was used for each side of the block. Post-operatively, Acetaminophen 1g IV 8 hourly was given to all patients, and in addition, Tramadol was used as rescue analgesia. Endpoints included comparing total Tramadol usage and Numerical Rating Scale scores between respective Groups.Results: Post-operative Tramadol consumption in Group-ESP was 144.26±16.38 mg compared with 200.58±17.57 mg of the Group-OSTAP. This difference was significant (p